The Effectiveness of Using Molly Polly Learning Media on Students' Understanding of Bullying at a Public Islamic Junior High School in Madiun - Ihwan Mahmudi; Rahma Raudah (Program Studi Bimbingan dan Konseling Islam, 2026)
ying is a serious problem in school environments that can hinder students’ psychological, social, and academic development, while limited understanding of its forms and impacts often causes bullying behavior to be perceived as normal. One learning medium that can be used to address this issue is Molly Polly, an educational board game adapted from Monopoly and designed to promote cooperation and critical thinking. This study aims to examine the effectiveness of Molly Polly learning media in improving students’ understanding of bullying at a public Islamic junior high school in Madiun. The study employed an experimental method using a pre-test–post-test control group design involving two eighth-grade classes with relatively equivalent academic characteristics, selected from the same population, with a total sample of 62 students. Data were collected using a validated 20-item multiple-choice test. The results showed a significant difference between the experimental and control groups, with mean post-test scores of 86.13 and 76.77, respectively. The Mann–Whitney U test indicated a significance value of 0.002 (< 0.05). These findings demonstrate that Molly Polly learning media is effective in enhancing students’ understanding of bullying and can serve as an alternative interactive learning medium for bullying prevention in schools.